The Influence of the Problem Based Learning Model Assisted by Student Worksheets (LKPD) on Student Learning Outcomes in the Material Kayanya Negeriku - Hastiarna, Ria; M. Ridwan Habibi; Munawir Gazali; Asrorul Azizi (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
This study aims to determine whether or not there is an effect of the Problem Based Learning model Assisted by Student Worksheets (LKPD) on student learning outcomes in the Kayanya Negeriku material at SD Negeri 2 Leneng in the 2022/2023 Academic Year. This study uses an experimental method with a Posttest-Only Control Design, which only provides a post-test at the end of the treatment. The population in this study were all fourth-grade students of SD Negeri 2 Leneng consisting of 2 classes, namely class IV.A and class IV.B. Meanwhile, the sample in this study was class IV.A as the experimental group and class IV.B as the control group. Both samples were selected randomly using the Cluster Random Sampling (Area Sampling) technique. The experimental group was given treatment with the Problem Based Learning model Assisted by Student Worksheets (LKPD) and the control group was taught with the conventional model. The research data were analyzed using a two-tailed t-test. Based on the research results, the t-hitung (4.513) > t-table (1.998) was obtained at a significance level of 0.05. Because , then H0 is rejected and Ha is accepted. Thus, it can be concluded that there is an influence of the Problem Based Learning Model assisted by Student Worksheets on student learning outcomes in the Kayanya Negeriku material at SD Negeri 2 Leneng in the 2022/2023 Academic Year.